2008
DOI: 10.1002/jts.20340
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of stressful life events throughout the life cycle to combat‐induced psychopathology

Abstract: This study examines the contribution of prewar life events, war exposure, and postwar life events to combat-induced psychopathology among 425 Israeli War veterans from the Lebanon War. Data was collected at two time points (1983 and 2002). The sample included veterans with and without combat stress reaction (CSR). Battle intensity and subjective experience of risk in war were associated with CSR. Negative childhood life events, CSR, PTSD in 1983 and postwar negative life events were associated with PTSD in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
(24 reference statements)
3
17
0
1
Order By: Relevance
“…Recent research has shown that posttraumatic stress symptoms (PTSS) and depressive symptoms are associated with traumas occurring before (Clancy et al, 2006; Maguen et al, 2008), during (e.g., Jacobson et al, 2008; Ramchand et al, 2011; Rona et al, 2009; Vogt et al, 2011; Wells et al, 2010), and after military service (Clancy et al, 2006; Solomon et al, 2008; Stein et al, 2005). Moreover, both childhood abuse history (Rosen & Martin, 1998) and mental health symptoms prior to deployment (Jacobson et al, 2008) are associated with alcohol use and alcohol-related problems.…”
Section: Alcohol Use and Trauma Exposure Among Male And Female Veteramentioning
confidence: 99%
“…Recent research has shown that posttraumatic stress symptoms (PTSS) and depressive symptoms are associated with traumas occurring before (Clancy et al, 2006; Maguen et al, 2008), during (e.g., Jacobson et al, 2008; Ramchand et al, 2011; Rona et al, 2009; Vogt et al, 2011; Wells et al, 2010), and after military service (Clancy et al, 2006; Solomon et al, 2008; Stein et al, 2005). Moreover, both childhood abuse history (Rosen & Martin, 1998) and mental health symptoms prior to deployment (Jacobson et al, 2008) are associated with alcohol use and alcohol-related problems.…”
Section: Alcohol Use and Trauma Exposure Among Male And Female Veteramentioning
confidence: 99%
“…It can heighten the risk for retraumatization as an increased dose of adversity (Harvey & Yehuda, 1999;Herman, 1992) often wears out one's strengths and generates further frailty in a continuous loss cycle (Hobfoll, 2002). Previously traumatized people are at a higher risk of developing posttraumatic stress disorder (PTSD) after a subsequent trauma (Solomon, Zur-Noah, Horesh, Zerach, & Keinan, 2008), especially when PTSD was already developed in response to prior trauma (Breslau, Peterson, & Schultz, 2008) and when the subsequent trauma was subjectively experienced as similar to the prior trauma (Solomon & Ginzburg, 1998).…”
mentioning
confidence: 98%
“…Having experienced and survived previous stressful incidents may reduce the impact of the stressor and enable more successful adaptation, the so called inoculation effect (Knight, Gatx, Heller, & Bengston, 2000;Norris & Murrell, 1988). Combat is traumatic and coping with additional stressors within that environment compounds the stress and the severity of the reaction (Solomon et al, 2008). Constant repetition of stress gradually depletes coping resources and makes the veteran more vulnerable to subsequent stressors.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Resilience is considered to be a culturally and contextually sensitive construct (Ungar, 2008). Some people appear to be able to tolerate stress without significant damage to their physical or psychological health; others cannot (Ungar, 2008) and this is possibly due to pre-war experiences and life course events (Solomon, Zur-Noah, Horesh, Zerach, & Keinan, 2008). A traumatic event is usually beyond a person's experience, and therefore difficult to understand (Horowitz, 1997).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%